Analysis of crisis response communication by U.S. Army Corps of Engineers, Tuttle Creek Lake, Kansas City District during the flooding crisis of 2019 - Schaeffer, Jessica Elise (Kansas State University, 2023)
In 2019, the Midwestern U.S. experienced extreme amounts of rainfall and snowmelt leading to a flooding crisis. One community under concern during the flooding crisis was Manhattan, Kansas, and surrounding towns because Tuttle Creek Lake, a lake utilized for flood control and managed by the U.S. Army Corps of Engineers (USACE), Kansas City District was operating at full capacity. For over 10 months, Tuttle Creek Lake operated in a flood crisis emergency mode. At one point the lake was so high, the water was close to overtopping the spillway gates put in place to help alleviate water elevation during a flood. A flood crisis is a stressful situation for all involved, but with clear and precise crisis communication, it is possible to communicate to the public what they need to know to stay informed. While Tuttle Creek Lake and the local community have had a strained history, USACE rangers work to serve the public through flood risk management and other Congressional purposes. With the rise in social media, communicating to the public about flood risk management includes social media like Facebook, in addition to traditional print media and radio. The purpose of this study was to understand the effectiveness of Tuttle Creek Lake’s Facebook communication via their posts during the 2019 flood crisis. One research objective and four research questions were used to guide this study including O1: Categorize and determine the frequency of initial U.S. Army Corps of Engineers Tuttle Creek Lake Facebook posts during the 2019 flood crisis; Q1: What Situational Crisis Communication Theory crisis response strategy or strategies did U.S. Army Corps of Engineers Tuttle Creek Lake publish on Facebook as posts during the 2019 flood threat?; Q2: What original Facebook posts by U.S. Army Corps of Engineers Tuttle Creek Lake generated the most organic public engagement through comments or reactions?; Q3: Did stakeholders express more positive or negative emotions through their responses and reactions on the U.S. Army Corps of Engineers Tuttle Creek Lake's Facebook posts with the most engaged posts during the 2019 flood threat?; Q4: Was there a timeframe during the flood threat when overall Facebook post engagement was the highest? This study used the Situational Crisis Communication Theory (SCCT) to categorize Tuttle Creek Lake’s Facebook posts into SCCT crisis response strategies. Once the SCCT strategies were determined, the posts were sorted through an excel sheet to find the top 15 most engaged posts for the primary and secondary strategies outlined by Situational Crisis Communication Theory. Once the top engaged posts were determined, a pattern for posts within a week of each other was also looked for. To understand how the USACE Facebook post crisis response strategies affected stakeholder emotions, this study utilized LIWC (Linguistic Inquiry and Word Count) to identify positive and negative emotions in the public’s comments to each Facebook post. The comments from the 30 top engaged Facebook posts were entered into LIWC, to understand if the stakeholders who commented expressed more positive or negative emotional reactions with their writing on the posts. Results show the crisis communication strategies used by Tuttle Creek Lake via Facebook posts elicited more positive than negative emotional responses by their stakeholders. The stakeholders were also more engaged during the highest lake elevation when the post engagement and timeline was observed. Recommendations include further research of other crisis communication of Tuttle Creek Lake’s Facebook posts for events such as the COVID-19 pandemic. Further research can study internal communication of park rangers during a flood event to see if the internal language becomes more positive or negative during peak flood times as well.
Keywords: Tuttle Creek Lake; Crisis communication; Situational Crisis Communication Theory; Social media